The Neuroanatomical Basis for Posterior Superior Parietal Lobule Control Lateralization of Visuospatial Attention - Wu, Yan; Wang, Jiaojian; Zhang, Yun; Zheng, Dingchen; Zhang, Jinfeng; Rong, Menglin; Wu, Huawang; Wang, Yinyan; Zhou, Ke; Jiang, Tianzi (Frontiers in Neuroanatomy, 2016)
The right hemispheric dominance in visuospatial attention in human brain has been well established. Converging evidence has documented that ventral posterior parietal cortex (PPC) plays an important role in visuospatial attention. The role of dorsal PPC subregions, especially the superior parietal lobule (SPL) in visuospatial attention is still controversial. In the current study, we used repetitive transcranial magnetic stimulation (rTMS) and diffusion magnetic resonance imaging (MRI) techniques to test the role of posterior SPL in visuospatial attention and to investigate the potential neuroanatomical basis for right hemisphere dominance in visuospatial function. TMS results unraveled that the right SPL predominantly mediated visuospatial attention compared to left SPL. Anatomical connections analyses between the posterior SPL and the intrahemispheric frontal subregions and the contralateral PPC revealed that right posterior SPL has stronger anatomical connections with the ipsilateral middle frontal gyrus, with the ipsilateral inferior frontal gyrus, and with contralateral PPC than that of the left posterior SPL. Furthermore, these asymmetric anatomical connections were closely related to behavioral performances. Our findings indicate that SPL plays a crucial role in regulating visuospatial attention, and dominance of visuospatial attention results from unbalanced interactions between the bilateral fronto-parietal networks and the interhemispheric parietal network.